RECENT UPDATE ON PRONIOSOMAL GEL AS TOPICAL DRUG DELIVERY SYSTEM - Rajkumar, Jampala; Gv, Radha; Sastri K, Trideva; Burada, Sadhana (Asian Journal of Pharmaceutical and Clinical Research, 2019)
An existence of transdermal delivery tool, proniosomal gel, has established to showed remarkable development for lipophilic/hydrophilic drugs over additional formulations. Newer drugs of lipophilic nature emerge poor bioavailability, irregular absorption, and pharmacokinetic changes. Therefore, this novel drug delivery system has been proved advantageous over other oral and topical delivery of drug candidates to bypass such disruption. This proniosomal gel basically is a compact semi-solid liquid crystalline (gel) composed of non-ionic surfactants easily formed on dissolving the surfactant in a minimal amount of acceptable solvent and the least amount of aqueous phase and phosphate buffer. Topical application of gel under occlusive condition during which they are converted into nisomes due to hydration by water in the skin present itself. Proniosomal gels are typically present in transparent, translucent, or white semisolid gel texture, which makes them physically stable throughout storage and transport. This review provides an important overview of the preparation, formulation, evaluation, and application of proniosome gel as a drug delivery carrier.